Desempenho diagnóstico do ultrassom pulmonar aliado ao esforço submáximo na detecção de congestão em pacientes ambulatoriais com ICFER - Tscheika, Anna Paula (2022)
Background: Heart failure (HF) is a chronic disease associated with great morbimortality. The 6-minute walk test (6MWT) is a submaximal exercise test useful in HF evaluation. Lung ultrasound (US) is a non-invasive tool capable of detecting congestion, including B-lines scan. There are no studies that combine the use of lung US with the 6MWT to detect congestion. Objective: To evaluate the diagnostic performance of lung US (appearance or increased number of B-lines) after the 6MWT. to detect congestion compared to a validated clinical score in outpatients with Heart Failure with Reduced Ejection Fraction (HFrEF). Methods: Patients with HFrEF were consecutively allocated from three HF outpatient clinics. After clinical and laboratory analysis to calculate the congestion score, patients wunderwent 6MWT and US blindly. Sensitivity and specificity, predictive values and receiver operating characteristic (ROC) curve were calculated with linear correction and measures of concordance. Results: Lung US after 6MWT demonstrated a regular discriminative performance to identify congestion when compared to the clinical score, with area under the curve (AUC) = 0.75 (95% confidence interval [95% CI]: 0.67-0.83). The presence of ≥ 6 Blines after stress test had a sensitivity of 48% and specificity of 84.4%, with positive post-test disease probability of 77% and negative of 40.3%. Resting lung US in relation to clinical score had AUC = 0.74 (95%CI: 0.65-0.82). There was no statistically significant difference between the diagnostic performance of US after stress and at rest (p = 0.493). Conclusion: Lung US after the 6MWT and at rest has a regular discriminative performance to identify congestion in relation to the clinical score. There was no difference between pulmonary US after stress and at rest.